Environmental philosophy : a revaluation of cosmopolitan ethics from an ecocentric standpoint - McDonald, H. P. (Value Inquiry Book Series, 2014)
Environmental Philosophy: A Revaluation of Cosmopolitan Ethics from an Ecocentric Standpoint calls for a new approach to ethics. Starting from the necessity for all life of air, water, and food, the book revalues the relation of ethics and environmentalism. Using insights of the environmental ethicists, environmental ethics becomes the model for ethics as a whole. Humans are part of a larger environment. Cosmopolitanism should be revised in accord with environmental ethics. The book applies a new theory of values to the relation of value and obligation, and of duty, rights and virtue, to accord with ecocentrism. The book also critically evaluates Utilitarianism and the self interest theory. Other chapters address population, species preservation and a practical program for environmental policy.